Characterization of monoclonal antibodies to protein antigen of Salmonella typhi. - Sarasombath, S (1988)
Two monoclonal antibodies were produced against protein antigens of Salmonella typhi. One of the antibodies (STP14) belongs to the immunoglobulin G1K subclass, and the other (STP13) was assigned to the immunoglobulin G2a(kappa) subclass. Both antibodies could recognize the 34.0-kilodalton protein antigen from S. typhi. The specificity of these antibodies was tested by immunoblotting with a panel of crude protein antigens from 12 bacteria causing enteric fever and enteric fever-like illness: S. typhi, S. paratyphi A, S. paratyphi B, S. paratyphi C, S. choleraesuis, S. enteritidis, S. krefeld, S. panama, S. typhimurium, Escherichia coli, Pseudomonas pseudomallei, and Yersinia enterocolitica. In a modified double-antibody sandwich enzyme-linked immunosorbent assay they could detect the protein antigen at ca. 0.6 microgram/ml. These monoclonal antibodies should be of great value in the diagnostic test for detecting S. typhi antigen in samples of bodily fluids isolated from patients with typhoid fever and in studies of the chemical structure and other immunological properties of this 34.0-kilodalton protein.